The Effectiveness of Schema Therapy on Sexual Aversion and Sexual Self-Efficacy - Ahmadzadeh, Hosna; Azadyekta , Mehrnaz; Bagheri , Fariborz (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aimed to evaluate the effectiveness of schema therapy on reducing sexual aversion and enhancing sexual self-efficacy. Methods: The research utilized a semi-experimental design with pre-test, post-test, and follow-up assessments. Thirty couples experiencing sexual aversion and low sexual self-efficacy were selected from counseling centers in Karaj, Iran. Participants were randomly assigned to either a schema therapy group (n=15) or a control group (n=15). The schema therapy group received 8 to 10 sessions of intervention. Two standardized questionnaires, the Sexual Self-Efficacy Questionnaire and the Sexual Aversion Inventory, were used to measure outcomes. Data were analyzed using multivariate analysis of covariance (MANCOVA), and follow-up tests were conducted to assess the stability of the intervention effects over time. Findings: The findings revealed that schema therapy significantly improved sexual self-efficacy and reduced sexual aversion in the experimental group compared to the control group (p < .01). These improvements were sustained during the follow-up phase, with no significant decline in outcomes. The post-test and follow-up results demonstrated that schema therapy had a lasting positive impact on participants’ sexual health. The control group, in contrast, showed no significant changes across the measurement phases. Conclusion: Schema therapy was found to be an effective intervention for reducing sexual aversion and increasing sexual self-efficacy. The sustained improvements suggest that schema therapy offers long-term benefits for individuals struggling with these sexual issues. This study highlights the importance of addressing early maladaptive schemas to improve sexual health and relationship satisfaction.